Detection of MYCN Gene Amplification in Neuroblastoma by Fluorescence In Situ Hybridization: A Pediatric Oncology Group Study - Mathew, Prasad (Nature Publishing Group, 2001)
To assess the utility of fluorescence in situ hybridization (FISH) for analysis of MYCN gene amplification in neuroblastoma, we compared this assay with Southern blot analysis using tumor specimens collected from 232 patients with presenting characteristics typical of this disease. The FISH technique identified MYCN amplification in 47 cases, compared with 39 by Southern blotting, thus increasing the total number of positive cases by 21%. The major cause of discordancy was a low fraction of tumor cells (≤30% replacement) in clinical specimens, which prevented an accurate estimate of MYCN copy number by Southern blotting. With FISH, by contrast, it was possible to analyze multiple interphase nuclei of tumor cells, regardless of the proportion of normal peripheral blood, bone marrow, or stromal cells in clinical samples. Thus, FISH could be performed accurately with very small numbers of tumor cells from touch preparations of needle biopsies. Moreover, this procedure allowed us to discern the heterogeneous pattern of MYCN amplification that is characteristic of neuroblastoma. We conclude that FISH improves the detection of MYCN gene amplification in childhood neuroblastomas in a clinical setting, thus facilitating therapeutic decisions based on the presence or absence of this prognostically important biologic marker.